Implementation Of Collaborative Learning To Develop Communication Skills Of Grade 4 Students SDN 2 For The Academic Year 2024/2025 - Nurmawadi Nurmawadi; Lalu Habiburrahman; Ana Mulyono (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to describe the implementation of collaborative learning to develop the communication skills of 4th-grade students at SDN 2 Selengen in the 2024/2025 academic year. The research question in this study is: How is collaborative learning implemented to develop the communication skills of 4th-grade students at SDN 2 Selengen? Collaborative learning encourages students to actively engage in discussions, exchange ideas, and work together to complete tasks, thereby providing ample space for strengthening both verbal and non-verbal communication skills.This study uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation during the learning process. The subjects of this study were the principal, the class teacher, and the students.The results of the study show that through collaborative learning activities, students had more opportunities to engage in discussions both to express their opinions and to listen actively. The findings also show that collaborative learning teaches students that within a group, all members share equal responsibility for completing the tasks assigned by the teacher. Thus, collaborative learning has proven effective in comprehensively developing students' communication skills.